2012
DOI: 10.1002/jcu.21923
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic features of histopathologically benign solid breast lesions that have been classified as BI‐RADS 4 on sonography

Abstract: BI-RADS category 4 lesions demonstrate more than one suspicious ultrasonography feature, and biopsy is necessary to diagnose malignancy captured in 33% of lesions in this study. At this time, any lesion with more than one suspicious BI-RADS US feature cannot avoid a diagnostic biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In general, Category 4 lesions require tissue sampling [49]. Previous study reported that heterogeneity, partially indistinct margin, and microlobulation are the most frequent suspicious findings leading to classifying a benign lesion as BI-RADS 4 [50]. If clinicians rely only on 2D ultrasound, excessive biopsies may be performed, consequently eliciting undesirable anxiousness in patients.…”
Section: Discussionmentioning
confidence: 99%
“…In general, Category 4 lesions require tissue sampling [49]. Previous study reported that heterogeneity, partially indistinct margin, and microlobulation are the most frequent suspicious findings leading to classifying a benign lesion as BI-RADS 4 [50]. If clinicians rely only on 2D ultrasound, excessive biopsies may be performed, consequently eliciting undesirable anxiousness in patients.…”
Section: Discussionmentioning
confidence: 99%
“…EIC of the breast typically appears as a smooth, round nodule, the nature of which cannot be detected through this method. Ultrasonographic imaging consistently achieved an accurate diagnosis (1,2,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)22,23,25,26), whilst mammography achieved accuracy in 79% of the reported cases (6)(7)(8)(9)(10)(11)(12)(15)(16)(17)(21)(22)(23)(24)(25)(26)(27). Magnetic resonance imaging was used in only 2 cases (16,25), but it was also observed to consistently identify EIC of the breast accurately.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging was used in only 2 cases (16,25), but it was also observed to consistently identify EIC of the breast accurately. FNAC (2,8,(16)(17)(18)(19)(25)(26)(27) and FNAB (1,2,7,8,14,15,18,22,23,25) may also aid the diagnosis, but these methods are less reliable when compared to ultrasonographic imaging. The present literature review demonstrated that ultrasonographic imaging is the diagnostic tool of choice to achieve the accurate characterization of EIC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely used for the BI-RADS classification of breast lesions in the clinic. However, the utility of ultrasound for breast lesions has been varied for some types of lesions, with a lack of specificity for some, or with overlap of benign and malignant signals [14] . Patients with mammary intraductal papillomas typically present with nipple discharge and lumps in the cancer area, which are characterized by catheter expansion and a hypoechoic lesions upon ultrasound examination.…”
Section: Discussionmentioning
confidence: 99%